Kearifan Lokal Manortor : Sebagai Jembatan Budaya dan Spiritualitas Batak Tarian Untuk Tuhan - Winda Kurniati Situmorang (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2025)
Manortor is a traditional Batak dance, which has long been an integral part of the culture and social life of the Batak people themselves. This dance, usually performed in traditional celebrations such as weddings, births, and other traditional ceremonies, functions as an expression of joy, prayer, and respect for ancestors. However, along with the entry of Christianity into the Batak community, Manortor underwent a significant transformation, shifting from a ritual of respect for ancestral spirits to a medium of worship and expression of faith in God. In the context of Christian theology,